Papillary Adenocarcinoma of the descending colon in a dog: Case report - Ferreira, M. G.P.A. [UNESP]; Ribeiro, J. O. [UNESP]; Pascoli, A. L. [UNESP]; Reis-Filho, N. P. [UNESP]; Beluque, T. [UNESP]; Santos, M. Q.P. [UNESP]; Theodoro, S. S. [UNESP]; Feliciano, M. A.R. [UNESP]; Nardi, A. B. [UNESP]; Tinucci-Costa, M. [UNESP]; Moraes, P. C. [UNESP]; Canola, J. C. [UNESP]; et al. (FapUNIFESP (SciELO), 2017)
The aim of this report was to describe the clinical findings and therapeutic management of a case of papillary adenocarcinoma of the descending colon in a Beagle. The patient presented soft stools, haematochezia, tenesmus, and dyschezia. Clinical examination revealed alterations on the ultrasonographic features of the descending colon suggestive of colitis and neoplasia. Following local mass resection, histopathology analysis revealed mild lymphoplasmocytic enteritis and papillary adenocarcinoma of the colon. Enterectomy for tumoral resection and biopsy of locoregional lymph nodes were carried out. Subsequent to the surgical procedure, it was possible to confirm the previous diagnosis and the tumor was classified as intestinal intraluminal papillary adenocarcinoma, with incomplete surgical margins. Adjuvant chemotherapy was performed using carboplatin, cyclophosphamide, and piroxicam, leading to remission of clinical signs and absence of any clinical or imaging alterations compatible with the patient's previous clinical condition.
Keywords: Canine; Intestinal neoplasia; Oncology